Diagnostic accuracy of three placement sites for the cold test in subjects amongst different age groups - Brenda Eréndida Castillo-Silva; Jorge Alejandro Alegría-Torres; Gabriel Alejandro Martínez-Castañón; Carlo Eduardo Medina-Solís; Norma Verónica Zavala-Alonso; Nereyda Niño-Martínez; Eva Concepción Aguirre-López; Nuria Patiño-Marín (BMC, 2019)
Abstract Background The cold test is a specific test of pulp sensitivity and is part of the endodontic diagnosis. The aim of this study was to identify the diagnostic accuracy including sensitivity, specificity, accuracy, positive predictive value and negative predictive value in three sites for the cold test in teeth with a need for endodontic treatment within different age groups from both genders. Methods A cross-sectional study was performed, evaluating 425 subjects. Two hundred and fifty-eight subjects from both genders from the ages of 17-27, 28-39, 40-50, and 51-65 years-old participated in the study. The cold test studied was 1, 1, 1, 2-tetrafluoroethane, and the gold standard was established through direct pulp inspection. The sites evaluated in the study were: The sites evaluated in the study were: a) the middle third of the buccal surface; b) the cervical third of the buccal surface, and c) the middle third of the lingual surface. Results The highest diagnosted accuracy was observed on the middle third buccal surface with an accuracy of = 0.97, a sensitivity of = 1.00, a specificity of 0.95, a predictive value of = 0.95 and a negative predictive value of = 1.00. This was in the female group aged from 40 to 50 years old. Conclusion The tables of this study can be used as an auxiliary for pulp sensitivity tests.